2017
DOI: 10.29037/ajstd.113
|View full text |Cite
|
Sign up to set email alerts
|

A New Triterpene Glycoside from the Sea Cucumber Holothuria Scabra Collected in Vietnam

Abstract: Bioassay guided fractionation led to the isolation of a new triterpene glycoside, holothurinogenin B (1) along with three known compounds, holothurin B (2), holothurin A (3), and holothurin A 2 (4), from the methanol extract of the Vietnamese sea cucumber Holothuria scabra. Their structures were deduced from the spectral analysis (1D-NMR, 2D-NMR, MS) and chemical evidences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…[3] The 1 H-NMR spectrum of 1 revealed four anomeric proton signals at δ in table 1. These data were similar to those reported, [4,5] confirming the sugar chain as 3-Omethyl-β-D-glucopyranosyl-(13)-β-D-glucopyranosyl-(14)-β-D-quinovopyranosyl-(12)-4-Osodium sulfate-β-D-xylopyranoside, one common tetraglycoside chain of saponins obtained from Holothuria species. [3] In addition, the 1 [5] Similarly, detailed analysis of the 1D, 2D NMR, and HR-QTOF-MS data as well as comparison of them with the literature values (table 1) led to identification of 3 and 4 as pervicoside C [7] and holothurin A, [4,5] respectively.…”
Section: Resultssupporting
confidence: 90%
“…[3] The 1 H-NMR spectrum of 1 revealed four anomeric proton signals at δ in table 1. These data were similar to those reported, [4,5] confirming the sugar chain as 3-Omethyl-β-D-glucopyranosyl-(13)-β-D-glucopyranosyl-(14)-β-D-quinovopyranosyl-(12)-4-Osodium sulfate-β-D-xylopyranoside, one common tetraglycoside chain of saponins obtained from Holothuria species. [3] In addition, the 1 [5] Similarly, detailed analysis of the 1D, 2D NMR, and HR-QTOF-MS data as well as comparison of them with the literature values (table 1) led to identification of 3 and 4 as pervicoside C [7] and holothurin A, [4,5] respectively.…”
Section: Resultssupporting
confidence: 90%
“…We recently demonstrated that trepang preparation does not significantly alter the saponin contents, compared to that of fresh animals. However, to the best of our knowledge, the saponin content of the viscera of H. scabra is, to date, not reported [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The monodesmosidic triterpene saponins of H. scabra consist of a holostanol-based aglycone and a C3-anchored glycan that is either linear or branched, and may contain up to 6 monosaccharide units (see Figure 1) [17,[37][38][39][40][41]. Honey-Escandón et al reported, in their review, the presence of sulfated and non-sulfated saponins in various organs of sea cucumbers, such as the body wall [17].…”
Section: Introductionmentioning
confidence: 99%
“…Please check your intended meaning is retainedOne aglycone and two saponins were tentatively identified comparing their m/z values to those reported in the literature. The peaks appearing at 15.86, 16.81, and 20.68 min are holothurinogenin B, holothurinoside K 1 , and philinopgenin B, respectively [34][35][36]. During this investigation, molecular ions with m/z values ranging from 200-800 [M + H] + were observed in abundance, indicating the presence of aglycones or saponins with low molecular weight.…”
Section: Phytochemical Profile Of H Atra Saponinmentioning
confidence: 79%